Modeling return in agricultural cooperatives and companies listed on the Tehran Stock Exchange - Ali Kiaei; Shahabeddin Sham; Amir Mohammadzadeh (تعاون و کشاورزی)
cooperative and stock companies play an important role in the country's economy. On the other hand, one of the most important and extensive financial researches is the explanation of the return in these companies. In the financial literature, identifying the factors influencing the return has always been of great importance. Based on this, the aim of the current research is to model returns in agricultural cooperatives and companies listed on the Tehran Stock Exchange.The current research is a quantitative research that is practical in terms of the type of goal. Also, it belongs to the group of descriptive and survey research. The statistical population of the research is all the cooperative companies active in the field of agriculture and all the companies accepted in the Tehran Stock Exchange. It includes 154 stock exchange companies and 52 agricultural cooperative companies.The research results showed that in both types of cooperative and stock exchange companies, size, profitability and leverage have a significant relationship with return. In companies listed on the Tehran Stock Exchange; The sentiment factor has no significant relationship with the return. The profitability factor has a positive and significant relationship with the return. The factor of value, size and leverage has a negative and significant relationship with the return. In agricultural cooperative companies; company size, return on asset, current ratio have a significant and positive relationship with return, and leverage has a negative and significant relationship with the return.